2019
DOI: 10.1186/s12879-019-4628-5
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and evolutionary characterization of norovirus GII.17 in the northern region of Brazil

Abstract: Background: Currently, norovirus (NoV) is associated with one-fifth of all acute gastroenteritis (AGE) cases worldwide. The NoV GII.17_2014 variant has been associated with gastroenteritis outbreaks in several Asian countries, replacing the previously dominant Sydney 2012 variant. There is limited data about circulation of this new strain in Brazil. This study aimed to describe the phylogenetic and evolutionary characteristics of the GII.17_ 2014 strains in the Northern region of Brazil. Methods: NoV was detec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 38 publications
0
7
0
1
Order By: Relevance
“…GII.P16/GII.4_Sydney recombinant. In the same period, it was observed the co-circulation of all circulating pandemic strains related worldwide in samples from Northern region of Brazil, including the GII.P16/GII.4 (Costa et al, 2019). In addition, Barreira et al (2017) detected GII.P16/GII.4 circulating in the Southeastern Brazilian coast state among children up 11 years old.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…GII.P16/GII.4_Sydney recombinant. In the same period, it was observed the co-circulation of all circulating pandemic strains related worldwide in samples from Northern region of Brazil, including the GII.P16/GII.4 (Costa et al, 2019). In addition, Barreira et al (2017) detected GII.P16/GII.4 circulating in the Southeastern Brazilian coast state among children up 11 years old.…”
Section: Discussionmentioning
confidence: 83%
“…The GII.P16/GII.4 strain emerged in the Amazon region in 2015 and was detected in 16.9% (16/95) of the cases during 2015-2016, being the second most prevalent virus since GII.P31/GII.4, which corresponded to 50.5% (48/95) of the NoV-positive cases (Costa et al, 2019). In this study, nucleotide analysis by BLASTn indicated that the strains circulating in Brazil had high identity with sequences of GII.P16/GII.4 from the United States (Barclay et al, 2019) and United Kingdom (Ruis et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in the Amazon states, between 2011 and 2014, the circulation of a recombinant strain GII.P7 / GII.6 was documented, which may indicate that this strain is already established in the population [2]. A recent study on samples collected during 2015 and 2016 from children under 5 years of age in Pará and Amazonas states demonstrated an increase in the circulation of the emerging GII.17_2014 strain in the Amazon region, and their phylogenetic approach suggests a single introduction of this genotype to the Amazon region [7]. Another strain that has also been detected in Amazonas is Gll.4, including variants GII.4 New Orleans_2009, and Sydney_2012 [2].…”
Section: North Regionmentioning
confidence: 92%
“…NoVs are strongly associated with acute non-bacterial gastroenteritis; they are highly infectious and can affect all ages. The main routes of transmission of these viruses vary between fecal-oral, contact with infected people, ingestion of contaminated food and/or water, and aerosol produced by vomiting [2,7]. Infection with these viruses is usually acute and limited: vomiting, diarrhea, and nausea are the main symptoms.…”
Section: Introductionmentioning
confidence: 99%